Data quality in Southeast Asia : analysis of official statistics and their institutional framework as a basis for capacity building and policy making in the ASEAN /: analysis of official statistics and their institutional framework as a basis for capacity building and policy making in the ASEAN. (2016) - Stagars, Manuel, 1974-
No abstract available